Positive impacts of livestock and wild ungulate routes on functioning of dryland ecosystems. Issue 20 (22nd September 2021) - Stavi, Ilan; Yizhaq, Hezi; Osem, Yagil; Argaman, Eli
Abstract: Livestock grazing is often perceived as being detrimental to the quality and functioning of dryland ecosystems. For example, a study in a semiarid Kenyan savanna proposed that cattle form bare spaces throughout the landscape, which indicate ecosystem degradation. Other studies, conducted in north‐eastern Spain, where climatic conditions range between semiarid and Mediterranean subhumid, reported that sheep and goat trails have increased the emergence of rill erosion processes. Sometimes, this negative perception is extended to include wild, large ungulate herbivores as well. Here, we challenge this perception by highlighting the generally nonadverse and even ameliorative impacts of moderate animal rate on geoecosystem functioning of hilly drylands. Specifically, trampling routes (also known as treading paths, livestock terracettes, cattle trails, migration tracks, cowtours, etc.) formed across hillslopes by grazing animals—being either domesticated livestock or native large herbivores—transform the original two‐phase vegetation mosaic of shrubby patches and interpatch spaces into a three‐phase mosaic. The animal routes increase the complexity of ecosystem, by strengthening the spatial redistribution of water and soil resources at the patch scale and decreasing hydrological connectivity at the hillslope scale. As a consequence, the animal routes improve functioning of hilly drylands and increase their resilience to long‐term droughts and climatic change. Therefore, instead of viewing the animal routes as degraded spots, they should be perceived at a wider perspective that allows to properly understand their overall role in sustaining dryland geoecosystems. Abstract : Livestock animals and wild ungulates form trampling routes across the landscape, transforming the original two‐phase vegetation mosaic into a three‐phase mosaic. The routes increase the complexity of ecosystems and decrease hydrological connectivity at the hillslope scale, thus improving ecological functioning and sustaining dryland durability under long‐term droughts and climatic change.